Efektivitas Pestisida Berbahan Nimba Terhadap Mortalitas Sitophilus zeamais (Coleoptera: Curculionidae) di Penyimpanan Biji-bijian - Purwatiningsih, Purwatiningsih; Alya, Fathia Anisa; Winarsa, Rudju; Muzakhar, Kahar (Mahesa Research Center, 2024)
Sitophilus zeamais is known as a warehouse pest insect that can cause damage to post-harvest crops by 0.5-2%. Effective control by considering food safety is the use of neem-based pesticides. This study aims to determine the effect of neem-based pesticides on S. zeamais mortality. The study was designed with a Completely Randomized Design (CRD) consisting of 6 treatments and 3 replications, with a spraying method. Measurement of feed weight before and after pesticide application was also observed. The results showed that neem-based pesticides had a significant effect on insects (p 0.05). Insect mortality at concentration of 0.5% showed the highest mortality with an average of 24%. Neem-based pesticide application also affected the amount of feed weight consumed by S. zeamais. At concentrations of 0.125%, 0.25% and 0.5%, the weight of feed consumed showed a decrease compared to concentrations of 1%, 2% and control. It can be concluded that pesticides containing active ingredients of neem at a concentration of 0.5% have the potential effect to control the activity of S. zeamais in post-harvest products based on the insect mortality and damage activity, especially on rice seeds.